Magnetic Modification and the Mechanism of Tb‐Phthalocyanine Single Molecule Magnets Prepared by a High Yield Method. Issue 21 (26th May 2020) - Ruan, Liuxia; Tong, Junwei; Qin, Gaowu; Zhou, Lianqun; Jiao, Xuechen; Zhang, Xianmin
Abstract : Lanthanide single‐molecule magnets are the most promising materials to be applied in the future spintronics applications. In this report, we firstly synthesize double‐decker Phthalocyanines (Pc), TbPc2 single‐molecule magnets and paramagnetic YPc2 by a straightforward solvothermal route with a yield up to 16 %, which is three times larger than that of conventional method. Their crystal structures and properties are systematically characterized by the matrix‐assisted laser desorption ionization–time‐off light mass spectrometry, X‐ray diffractometer, Ultraviolet–visible spectra, Fourier transform infrared spectra, X‐ray photoemission spectroscopy, near‐edge X‐ray absorption fine structure (NEXAFS) spectroscopy, Inductive Coupled Plasma Emission Spectrometer and magnetic measurements. The NEXAFS spectroscopy confirms that a strong peak at 401 eV emerges not YPc2 but TbPc2, clearly indicating the different electronic structures of YPc2 and TbPc2 . A typical hysteresis loop of single molecule magnet is observed for TbPc2 . While, YPc2 shows a paramagnetic character. The SMM property of TbPc2 modified by introducing YPc2 was studied in detail. The maximum hysteresis area appears for the sample with Tb/Y = 7:3, which obviously demonstrates the concentration of YPc2 affects magnetic relaxation process by varying the intermolecular interactions of TbPc2 . The barrier energy fitted from the results of alternating‐current magnetic susceptibility is 740 K for TbPc2 and 781 K for the sample with Tb/Y = 7:3, further indicating that the isolation of neighbor Tb ions by Y ions could slow down the flip of magnetic dipole. Abstract : Single‐molecule magnetic TbPc2 and paramagnetic YPc2 were successfully prepared with a high yield. Magnetic dilution of TbPc2 by YPc2 was systematically investigated, indicating that the optimal dilution can slow down the flip of magnetic dipole. This study contributes to the exploration of new synthetic method and the further understanding of magnetic relaxation mechanisms for novel single‐molecule magnets.